Religion, class, and the postwar development of the Dutch welfare state - Oude Nijhuis, Dennie (Amsterdam University Press, 2018)
This book examines how the Netherlands managed to create and maintain one of the world's most generous and inclusive welfare systems despite having been dominated by Christian-democratic or "conservative" rather than socialist-dominated governments for most of the post-war period. It emphasises that such systems have strong consequences for the distribution of income and risk among different segments of society and shows that they could consequently only emerge in countries where middle class groups were unable to utilise their key electoral and strong labour market position to mobilise against this. The book argues that this calls for a major reconsideration of the roles of Christian-democracy and the labour union movement in the development of modern welfare states. By highlighting how welfare reform contributed to the employment miracle of the 1990s, the book also sheds new light on how countries are able to combine high levels of welfare generosity and solidarity with successful macro-economic performance.